Investigation of glyphosate removal from aqueous solution using calcium peroxide - Li, F.; Choong, T. S. Y.; Abdullah, L. C.; Md Jamil, S. N. A . (IOP Publishing, 2022)
Glyphosate, an organophosphate herbicide containing carboxyl group, is widely used in agriculture. It can be found as a contaminant in water, and procedures are required for its removal. The present study investigated the efficiency of glyphosate removal from aqueous solutions using a Fenton-like system. Calcium peroxide (CaO2) was used as a source of hydroxyl free radicals with Fe2+ as the catalyst to trigger Fenton reaction. Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and potassium permanganate titration were carried out for characterization of calcium peroxide. The effect of operating parameters such as pH, molar ratio of Ca2+: Fe2+, and initial dosage of calcium peroxide on the total phosphorus (TP) removal efficiency was studied. The maximum TP removal was 94.50% under optimal conditions (pH = 3.0, initial glyphosate concentration = 50 ppm, initial CaO2 dosage = 0.5 g, molar ratio of Ca2+: Fe2+= 6). This study demonstrated that calcium peroxide could be considered as an effective oxidant for glyphosate wastewater treatment.